Pathophysiological basis of West Syndrome: Literature review (Research, Society and Development, 2024)
West Syndrome is an epileptic encephalopathy composed of a triad: muscle spasms, predominantly in clusters, delay in neuropsychomotor development and hypsarrhythmia observed on the electroencephalogram. The pathophysiology is not yet fully understood. The most commonly used diagnostic methods today are EEG, which is performed in all cases, computed tomography and transfontanellar ultrasound. Studies on preferred drug therapy are inconclusive, suggesting multiple treatment and dosage options. The lack of knowledge of West Syndrome on the part of the primary health care medical team leads to late diagnosis, which delays treatment, culminating in delayed neuropsychomotor development that may be irreversible. This article aims to analyze the intrinsic characteristics of the disease, as well as pathophysiology, clinical picture, diagnostic and therapeutic advances. The methodology consists of an integrative literature review. Therefore, the development of research on the pathophysiology of the disease to determine new therapies is essential, leading to the search for improving the restricted prognosis and quality of life, guaranteeing better survival of patients with West syndrome.